Factors affecting immunization among children of rural population of block Malpura, district Tonk, Rajasthan, India - Singhal, Govind; Mathur, H. N.; Dixit, Mukul; Khandelwal, Anmol (International Journal Of Community Medicine And Public Health, 2017)
Background: Immunization is a highly cost effective way of improving child survival, however it is estimated that every year, at least 27 million children worldwide do not receive the basic package of immunizations. In India, immunization services are offered free in public health facilities, but the immunization rate remains low. The Routine Immunization schedule includes BCG, OPV, DPT, hepatitis B, and measles vaccines. Now heamophillus influenza B, DPT and hepatitis B are given combined as a pentavalent vaccine since September 2014 in Rajasthan. Objectives of the study are, to determine immunization coverage status of infants and to know about socio-demographic factors influencing infant immunization. Methods:A cross-sectional study included 210 caretakers and infants of 12-23 months old selected by applying the 30 × 7 cluster sampling method in block Malpura during the period of March 2015 to April 2015. Only one infant was selected from each care taker. Results: It was observed that 149 (70.96%) of the subjects had complete immunization while 50 (23.80%) had partial and 11 (5.24%) had no immunization coverage. Complete immunization was observed better in Hindu families of 121 (81.20%) subjects. Literacy status of parents is related to high immunization coverage as observed that 105 (70.47%) mothers and 111 (74.49%) fathers were literate out of 149 completely immunized subjects. Immunization coverage was observed better among children delivered at institutions as 132 (88.59%) out of 149 completely immunized subjects delivered at institutions whereas 23 (46%) from partially immunized and 06 (54.54%) from non-immunized were delivered at home. The commonest reason among partial and non-immunized infant was sickness 22 (36.06%) of elder sibling as a result of the previous vaccination followed by 20 (32.07%) of the sickness of beneficiary at the time of vaccination. Conclusions:There is good immunization coverage observed in this rural block but to achieve the goal of vaccine preventable diseases and the millennium development goal of reducing child mortality, we have to strengthen routine immunization services and also to motivate the community as well as health care providers to follow the National Immunization Programme.